Analysis of Family Support with Diabetes Self-Management in Type II Diabetes Mellitus Patients - Patoding, Seprinus; Fadli, Fadli; Hartono, Hartono (Althar Cendikia Education, 2024)
Family support is crucial in changing the condition of patients with diabetes mellitus. If a patient lacks family support, it will affect their self-management. Diabetes self-management refers to the knowledge of properly managing diabetes mellitus (DM) by controlling the disease through problem-solving skills development and increasing patients' self-confidence to reduce the impact of diabetes. The aim of this study is to determine the relationship between emotional, instrumental, appreciation, and informational support with diabetes self-management in patients with type 2 DM in the working area of Wara Barat Public Health Center, Palopo City, in 2024. This research is a quantitative study with a descriptive-analytical research design using a cross-sectional approach. The sample size consists of 65 respondents selected through purposive sampling. The research instrument includes the HDFSS family support questionnaire and the DMSQ diabetes self-management questionnaire. Based on the chi-square test results, the p-value was found to be <0 (α<0.05), indicating a relationship between family support—viewed from four dimensions: emotional, instrumental, informational, and appreciation—and diabetes self-management in type 2 DM patients in the working area of Wara Barat Public Health Center, Palopo City, in 2024. It is recommended that families of type 2 DM patients who still lack sufficient family support better understand the self-management needs of the patients.